Temperature control circuit for surface acoustic wave (SAW) resonators - Ashari, Zainab; Sidek, Fatini; Nordin, Anis Nurashikin (IIUM Press, 2011)
Surface Acoustic Wave (SAW) resonators are key components in oscillators, frequency synthesizers and transceivers. One of the drawbacks of a SAW resonator is that its piezoelectric substrate is highly sensitive to ambient temperatures which results in performance degradation. This work proposes a simple circuit design which stabilizes the temperature of a SAW resonator, making it independent of temperature changes. This circuit is based on the oven control method which elevates the temperature of the resonator to a temperature high enough for it to become tolerant to minor changes in ambient temperatures.The circuit consists of a temperature sensor, a heater and a comparator which turns the heater ON (or OFF) depending on the ambient temperature. Several SAW resonators are tested using this circuit and the experimental results indicate reduction in the Temperature Coefficient of Frequency (TCF from a maximum value of 130.44/°C to a minimum of -1.11/°C.